An audit of clinical practice in the management of head injured patients following the introduction of the Scottish Intercollegiate Guidelines Network (SIGN) recommendations. Issue 12 (18th November 2005) - Kerr, J; Smith, R; Gray, S; Beard, D; Robertson, C E
Abstract : A prospective study was conducted by the Scottish Trauma Audit Group (STAG) in A&E of Edinburgh Royal Infirmary to examine clinical practices in the management of head injured patients pre- and post-inception of the SIGN guidelines published in August 2000. 1607 patients attended the department in two separate one month periods at equal intervals pre- and post-guidelines publication. The majority of patients with a SIGN indication for admission were admitted (93% pre- and 92% post-guidelines). For skull x ray (SXR) requests, in the pre-guidelines group, 92% of admitted patients with a SIGN indication for x ray had a SXR: this figure dropped to 79% post-guidelines. 36% of patients with a SIGN indication for CT actually had a scan pre-guidelines: this figure increased to 64% post-guidelines. 57% of patients pre-guidelines and 44% of patients post-guidelines were discharged from A&E in accordance with the SIGN recommendations. Of patients admitted for neurological observations, this increased from 50% pre- to 88% post-guidelines. Of patients who were discharged "inappropriately", only one re-presented and was subsequently admitted but required no neurosurgical intervention. Despite publication of the SIGN guidelines and positive reinforcement in A&E and at ward level, practice has not changed significantly. Where our practice did not adhere to SIGN recommendations, there was no untoward sequelae. For published national guidelines to be effective, a formal audit structure with regular feedback is necessary to ensure a continued change in clinical practices.